SEXUAL DISFUNCTION RELATIONSHIP WITH QUALITY OF LIFE IN DIABETES MELLITUS PATIENTS IN NGANJUK DISTRICT - Cahyono, Sony Wahyu Tri; Kurnyawati, Nerilita Turis; Purwandari, Henny (LPPM STIKes SATRIA BHAKTI NGANJUK, 2022)
The research design used a correlation with a cross sectional approach. The study population was all male respondents with diabetes mellitus who visited the Sawahan Health Center, Nganjuk Regency, a total of 29 patients and samples that met the inclusion criteria of 25 patients were taken using accidental sampling technique. The independent variable was sexual dysfunction measured by IIEF and the dependent variable was quality of life measured by WHOQOL-BREF. Statistical test using Spearman's rho with = 0.05 on SPSS20. The results showed that from a sample of 25 patients with diabetes mellitus, it was known that almost half of them were in the category of mild to moderate sexual dysfunction as many as 10 patients (40%) and most of them were included in the category of adequate quality of life as many as 14 patients (56%). Spearman's rho test results value = 0.015 = 0.05 so that Ha is accepted. It can be concluded from this study that there is a relationship between sexual dysfunction and quality of life in patients with diabetes mellitus at the Sawahan Health Center, Nganjuk Regency.